Early open mitral valve surgery following arterial embolism. Issue 3 (May 1970) - Borman, J. B.; Merin, G; Romanoff, H.; Milwidsky, H.
Abstract : A report is presented of nine patients who underwent early open mitral valve surgery after arterial embolism had occurred. Five of these patients suffered an early second arterial embolism before their mitral operation, an observation which stresses the risk inherent in delay of mitral valve surgery. The demonstration of atrial thrombi in four illustrates the potential danger of closed valvotomy techniques in such cases. Advanced pathological changes and severe stenosis of the mitral valve were found in all nine patients; valve replacement had to be done in three. All nine patients are alive and well after follow-up from 6 to 42 months. No further thromboembolic events have occurred after mitral valve surgery.